Upregulation of lipocalin-2 in human papillomavirus-positive keratinocytes and cutaneous squamous cell carcinomas. - Akgül, B; Bauer, B; Zigrino, P; Storey, A; Mauch, C; Pfister, H (2011)
It has been demonstrated previously that E7 oncogene expression of human papillomavirus (HPV) type 8 in keratinocytes induces cell invasion and accelerated differentiation. Looking for cellular genes deregulated by HPV-8 E7, lipocalin-2 was identified as being upregulated in these cells by cDNA microarray analysis. Lipocalin-2 is known to be overexpressed in many human cancers and is implicated in the regulation of cell proliferation, differentiation and apoptosis. In this study, increased levels of lipocalin-2 were observed in extracts from HPV-8 E7-positive keratinocytes and from keratinocytes expressing E7 of HPV-1, -4, -5, -15, -20 and -38, but not of HPV-16. Similar results were obtained when measuring secreted lipocalin-2 in the supernatants of the cell cultures. Lipocalin-2 expression was associated with cell differentiation in keratinocyte monolayers and in organotypic skin cultures. It was found in the uppermost layers of HPV-5, -8, -15, -16, -20 and 38 E7-expressing but not low-risk HPV-1 and -4 E7-expressing keratinocytes. Immunohistochemical staining of HPV-positive and -negative human skin squamous cell carcinomas (SCCs) revealed lipocalin-2 expression mostly in differentiated, filaggrin-positive areas of 15 out of 17 HPV-positive and three out of nine HPV-negative SCCs. These data indicate that lipocalin-2 expression correlates with HPV positivity of cutaneous SCCs.